2015
DOI: 10.1515/humor-2015-0099
|View full text |Cite
|
Sign up to set email alerts
|

A dual-processing approach to the effects of viewing political comedy

Abstract: Stephen Colbert’s announcement that he would take over

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Both comedy and music have also been found to be effective within educational contexts in and out of a classroom setting. In previous studies, comedy improved short-term issue recognition, something that corresponds to memory results of online learning (Warner et al 2015;Southwick et al 2002). Furthermore, a teaching tool such as comedic Theoretical Theatre, where teachers "portray characters who physically embody different theories in interactive scenarios including a Question Time-style debate, a chat-show, or a date", has been analysed as a case study and researchers have suggested that it could help ground theoretical material in the classroom compared to traditional lectures (Gravey et al 2017).…”
Section: Combining the Effects Of Comedy And Music In The Classroommentioning
confidence: 55%
See 2 more Smart Citations
“…Both comedy and music have also been found to be effective within educational contexts in and out of a classroom setting. In previous studies, comedy improved short-term issue recognition, something that corresponds to memory results of online learning (Warner et al 2015;Southwick et al 2002). Furthermore, a teaching tool such as comedic Theoretical Theatre, where teachers "portray characters who physically embody different theories in interactive scenarios including a Question Time-style debate, a chat-show, or a date", has been analysed as a case study and researchers have suggested that it could help ground theoretical material in the classroom compared to traditional lectures (Gravey et al 2017).…”
Section: Combining the Effects Of Comedy And Music In The Classroommentioning
confidence: 55%
“…For example, late-night talk shows such as The Daily Show include political issues with a comedic spin and have been shown to cover similar levels of news information as mainstream broadcast journalism (Brewer & Marquardt 2007;Feldman 2007), serving as a source of entertaining information since it first aired in 1996 in the United States. Similarly, comedic videos have also been shown to encourage audiences to think critically about manipulative media messages and weak arguments, for example when exposed to comedian Stephen Colbert's Super PAC video programming that "generated modest short-term issue recognition characteristic of online learning" (Warner et al 2015). Comedy in the media has also been shown to be effective in challenging gender roles and femininity through characters who did not fit traditional molds such as Lucille Ball in the 1950s (White 2016) and in educating audiences about racial issues and reducing racial tension such as with Chris Rock and Dave Chappelle starting in the 1980s (Green & Linders 2016).…”
Section: Informative Comedymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to inattentiveness to politics, resulting into 'rational ignorance', there is an increased tendency of political manipulation of politically apathetic citizens (Fishkin, 2009;Zaller, 1991), particularly in the elite-dominated public sphere of the mainstream media (Mustapha & Omar, 2020).Thus, it has been held that the transition to 'high choice' media environment of digital and social media has improved the political involvement among those who consume news rather than entertainment (Prior, 2005).Conversely, other studies conducted in this changing media environment have documented pockets of evidence signalling significant contributions of entertainment preference on political participation among social media users (Chen, 2017;Yu, 2016).Findings supporting influence of social media political satire on youths' political participation are instances of significant contribution of entertainment content to political engagement (Mustapha et al, 2019;Warner et al, 2015).These mixed findings necessitate further investigation into motivations for social media use and their attendant consequences on political participation, especially in a relatively young democracy like Nigeria's. Having research rooted in contexts other than those proposed by an academy that mostly writes from and for the Global North is an imperative if we, as social scientists, want to have a broad perspective to analyse the reality that surrounds us.…”
Section: Introductionmentioning
confidence: 99%
“…This line of research has also tested for the learning effect of exposure to political satire (Feldman, 2013;Hardy et al, 2014;Y. M. Kim & Vishak, 2008; Benjamin R. Warner, Hawthorne, & Hawthorne, 2015). Based on the by-product learning hypothesis (Baum, 2002) and gateway hypothesis (Baum, 2003b), Baum argues that entertainment or comedy associated with soft news reduces the cognitive costs associated with learning about politics in the first place.…”
Section: Chapter 2: Theoretical Review Political Satirementioning
confidence: 99%